Modeling and analysis of security incidents for mobile communication mesh Zigbee-based network - Desnitsky, V. A.; Kotenko, I. V. (2017 XX IEEE International Conference on Soft Computing and Measurements (SCM), 2017)
The paper is aimed at researching the subject area, models and prototypes of secure mobile communication mesh networks providing support and operational management in critical emergency situations. Such a network represents a command technical complex that provides services of text messages and media data transfer, database services, web services, etc. A two-layer network architecture using Arduino microcontrollers and XBee Series 2 modules, implementing business processes and wireless communications by ZigBee protocol is proposed. The two-layer character of the network allows organizing isolation of data flows between particular subnets, nodes and users effectively. Methods of analytical modeling and simulation of intruder actions on the base of a generalized intruder model of embedded devices are applied. Experiments were conducted to simulate security incidents and detect them on the physical implementation of the mobile communication network prototype.